The development of ToF-SIMS for in-situ glycosaminoglycan analysis - Milne, Lorna (2025)
Glycosaminoglycans (GAGs) are linear polysaccharide chains composed of repeating disaccharide units with essential roles in several biological processes from embryonic patterning to modulation of blood vessel permeability. Despite their biological importance, GAG analysis is limited by a lack of available tools that can provide simultaneous spatial and compositional analysis. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) is a method of mass spectrometry imaging that enables the collection of compositional analysis through the generation of mass spectra, and spatial analysis through the conversion of spectra to an image. Previous utilisation of ToF-SIMS for in-situ GAG analysis has focussed on sulphate-containing ions that provide minimal compositional information. In the approach presented here, a series of knockout cells lines mutant for components of the GAG biosynthetic pathway are analysed to generate and validate a library of SIMS ions that discriminate between different GAG types, including both sulphated and non-sulphated. These ions were acquired from biological samples that contain a milieu of biomolecules. Through the analysis of cell lines carrying knockouts of specific sulphotransferases, ions were identified that were discriminatory of both heparan sulphate (HS) and chondroitin sulphate (CS) sulphation modifications. To the best of our knowledge, this is the first example of the use of knockout cell lines to validate the likely biological origin of a SIMS ion. Methods of multi variant analysis were optimised to enable the use of ions non-discriminatory of individual GAG types to act as an initial screening tool to identify GAG related changes in samples. Principal component analysis and partial least square regression discriminant analysis could use the intensity of such ions to discriminate between wild type (WT) and GAG synthetic mutant cell lines.